2021
DOI: 10.3389/fpsyg.2021.573924
|View full text |Cite
|
Sign up to set email alerts
|

Drivers or Drifters? The “Who” and “Why” of Leader Role Occupancy—A Mixed-Method Study

Abstract: This study investigated the reasons that leaders have given for their leader role occupancy. By using a mixed-method approach and large leader data, we aimed to provide a more nuanced picture of how leader positions are occupied in real life. We examined how individual leadership motivation may associate with other reasons for leader role occupancy. In addition, we aimed to integrate the different reasons behind leader role occupancy into the framework of sustainable leader careers and its two indicators: lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…Although AI-MTL marginally strengthened the association between intensified career-related demands and exhaustion, it still seems that AI-MTL (i.e., intrinsic motivation toward leadership) functions, to some extent, as a personal resource for leaders to fight exhaustion. This supports previous findings about AI-MTL as a resource for leaders ( Auvinen et al, 2020 , 2021 ). Leaders with high AI-MTL are more likely to experience leadership self-efficacy ( Chan and Drasgow, 2001 ; Badura et al, 2020 ) which may enhance the experience of controlling the overall picture.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although AI-MTL marginally strengthened the association between intensified career-related demands and exhaustion, it still seems that AI-MTL (i.e., intrinsic motivation toward leadership) functions, to some extent, as a personal resource for leaders to fight exhaustion. This supports previous findings about AI-MTL as a resource for leaders ( Auvinen et al, 2020 , 2021 ). Leaders with high AI-MTL are more likely to experience leadership self-efficacy ( Chan and Drasgow, 2001 ; Badura et al, 2020 ) which may enhance the experience of controlling the overall picture.…”
Section: Discussionsupporting
confidence: 92%
“…This study has contributed to the literature on the motivation to lead, building on the previous research of AI-MTL in the context of sustainable careers and resources ( Auvinen et al, 2020 , 2021 ). We found that intensified learning demands at work may be associated with feelings of inadequacy 2 years later.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations